PIK3CA and TP53 MUTATIONS and SALL4, PTEN and PIK3R1 GENE EXPRESSION LEVELS in BREAST CANCER - KAYA, HANDAN; ERBARUT SEVEN, İPEK; GÜLLÜOĞLU, MAHMUT BAHADIR; AKKİPRİK, MUSTAFA; UĞURLU, MUSTAFA ÜMİT; ÖZER, SIDIKA AYŞE (WALTER DE GRUYTER GMBH, 2020)
Objective: A high frequency of PI3K signalling pathway abnormalities and TP53 mutations are critical in the development and progression of breast cancer (BCa). We aimed to detect PIK3CA and TP53 mutations via an expression analysis of PIK3R1, PTEN and SALL4 and correlate the expression of these genes with clinical parameters of BCa. Materials and methods: PIK3CA and TP53 mutations in BCa samples were analysed by High-Resolution Melting (HRM) analysis, followed by Sanger sequencing, and the expression levels of PIK3R1, PTEN and SALL4 were evaluated by RT-PCR methods. Results: The frequency of PIK3CA and TP53 mutations was 42% and 38% according to the HRM and Sanger sequencing. There was a significantly high frequency of these mutations in ER(+), N0 and HER2(-) tumour samples. PIK3R1 and PTEN expression levels were high in tumour samples, whereas SALL4 expression was low. In patients with TP53 mutations, PIK3R1 expression was low, and this finding was statistically significant. PIK3R1 and PTEN expression levels showed statistically significant, respectively in G3 grades, ER(+), (PR)(+), HER2(+) and ER(+). Conclusions: We suggest that these candidate genes could be potential prognostic biomarkers of BCa and that they should be considered in the evaluation of clinical parameters of BCa.
Keywords: Breast cancer; PI3K; PIK3CA; HRM; Candidate genes; CELL-PROLIFERATION; ASSOCIATION